Analisis Kadar Air Gelatin Kulit Ayam Hasil Ekstraksi Menggunakan Metode Waterbath dan Sonikasi - Angelica Vidya Ulfa; Miftahul Khair (Lembaga Yasin AlSys, 2025)
Gelatin is a collagen-derived product widely utilized in the food, pharmaceutical, and cosmetic industries, with moisture content being a critical quality parameter. This study aims to evaluate the effect of extraction methods on the moisture content of gelatin derived from chicken skin, using two different approaches: conventional waterbath and ultrasound-assisted extraction (sonication). The extraction process began with acid hydrolysis using citric acid, followed by waterbath treatment at 65 °C for 10, 20, and 30 minutes, and sonication at a frequency of 47 kHz for 10–50 minutes. Samples with the highest yield from each method (10-minute waterbath and 50-minute sonication) were analyzed for moisture content. The results showed that gelatin obtained via sonication had a moisture content of 9.51 ± 0.70%, while that obtained via waterbath was 10.21 ± 2.15%. A paired t-test yielded a p-value of 0.641, indicating that the difference in moisture content between the two methods was not statistically significant. Both values remain within the acceptable limit set by the Indonesian National Standard (SNI 01-3735-1995), which stipulates a maximum moisture content of 16%. Thus, both conventional and sonication methods are capable of producing high-quality gelatin in terms of moisture content, with slightly higher drying efficiency observed in the sonication method.